Evolution of agricultural mechanization in Vietnam: Insights from a literature review and multiple rounds of a farm household survey - Takeshima, Hiroyuki; Liu, Yanyan; Nguyen, Cuong Van; Masias, Ian (International Food Policy Research Institute, 2019)
Vietnam has experienced rapid growth in agricultural mechani-zation lately; particularly in the use of tractors and combine-harvesters. A recent IFPRI study documented the evolution of the growth of mechanization in Vietnam based on an extensive review of the existing literature and several rounds of a nationally repre-sentative household survey. The level of tractor use in Vietnam was relatively high in the 1970s and the early 1980s but declined through the late-1980s before it started taking off again in the 1990s. The relatively high level of tractor uses up to the early-1980s were partly due to political and military reasons, as both the West and the Soviet Union gave substantial support in providing heavy machinery, including tractors. In this note, we focus on the evolution of mechanization from 1990s to 2000s.